Histomorphometric changes of testicular tissues by season and age of Algerian local donkeys (Equus asinus) - Sofiane Aissanou; Abdelhanine Ayad (Acta Scientiarum. Animal Sciences, 2022)
The present investigation was undertaken to highlight the histomorphometric changes of testicular tissues according to season and age in donkeys (Equus asinus) under northern Algeria conditions. The experiment was conducted from February 2019 to January 2020. A total of 21 sexually mature donkeys were selected randomly. The testis were immediately collected after slaughter for the histological observation. The analysis of the correlation coefficients shows negative correlations between DL and other parameters such as DST, GCEH, TTA and ITSA, ranged between -0.24 and -0.79. Also, there were a high negative correlations between season and the histomorphometric parameters, except DL was revealed positive (r=0.65). On the other hand, there were positive correlations between age and testicular histomorphometrics parameters. The results indicated that DST, GCEH, TTA and ITSA values were significantly higher in winter and autumn seasons than in spring and summer seasons. It is also noteworthy that DST, GCEH, TTA and ITSA values were significantly higher in adult and aged donkeys than in young donkeys. Our comparative analysis of histological parameters, suggests that the sexual activity usually occurs during winter and autumn in local donkeys of Algeria. In addition, our results of histomorphometric of testicular tissues are correlated with age of donkeys.